Temporal variability of aerosol optical thickness vertical distribution observed from CALIOP. Issue 15 (8th August 2016) - Toth, Travis D.; Zhang, Jianglong; Campbell, James R.; Reid, Jeffrey S.; Vaughan, Mark A.
Abstract: Temporal variability in the vertical distribution of aerosol optical thickness (AOT) derived from the 0.532 µm aerosol extinction coefficient is described using Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) observations over 8.5 years (June 2006 to December 2014). Temporal variability of CALIOP column‐integrated AOT is largely consistent with total column AOT trends from several passive satellite sensors, such as the Moderate Resolution Imaging Spectroradiometer, Multiangle Imaging Spectroradiometer, and the Sea‐viewing Wide Field‐of‐view Sensor. Globally, a 0.0002 AOT per year positive trend in deseasonalized CALIOP total column AOT for daytime conditions is attributed to corresponding changes in near‐surface (i.e., 0.0–0.5 km or 0.5–1.0 km above ground level (agl)) aerosol particle loading, while a −0.0006 AOT per year trend during nighttime is attributed to elevated (i.e., 1.0–2.0 km or >2.0 km agl) aerosols. Regionally, increasing daytime CALIOP AOTs are found over Southern Africa and India, mostly due to changes in aerosol loading at the 1.0–2.0 km and 0.0–0.5 km agl layers, respectively. Decreasing daytime CALIOP AOTs are observed over Northern Africa, Eastern U.S., and South America (due mostly to elevated aerosol loading), while the negative CALIOP AOT trends found over Eastern China, Europe, and Western U.S. are due mostly to aerosol layers nearer the surface. To our knowledge, this study is the first to provide both a globally comprehensive estimation of the temporal variation in aerosol vertical distribution and an insight into passive sensor column AOT trends in the vertical domain. Key Points: Near‐zero trends in CALIOP column AOT are found globally Regionally, trends in CALIOP column AOT and their sources vertically are quantified Total column AOT trends derived from both passive and active sensors are consistent for most regions